Температурно-аномальная диффузия в недодемпфированных периодических системах - Марченко, Игорь Иванович; Жигло, Андрей Валентинович; Марченко, Иван Григорьевич (НТУ "ХПИ", 2016)
В работе исследовано усиление диффузии частиц в пространственно-периодических структурах под воздействием периодических во времени полей. Показано, что диффузия может быть произвольным образом усилена (на многие порядки) при выборе соответствующих температур, амплитуд и частот внешнего поля. Установлено, что при амплитудах превышающих критический уровень, в температурной зависимости возникает область температурно–аномальной диффузии (ТАД) при которой коэффициент диффузии возрастает с понижением температуры.

We have investigated the strengthening of the diffusion of particles in a spatially periodic structures under the influence of periodic in time fields. It is shown that diffusion can be arbitrarily enhanced (many orders of magnitude) in the selection of appropriate temperatures, amplitudes and frequencies of the external field. The physical reason behind the strong diffusivity enhancement is emergence of two populations of partic les under the action of external force, locked and running ones. At optimal forces and temperature the number of particles in the two populations is comparable, long flights of therunning particles relative to the locked population take place with significant probability, resulting in giant enhancement of diffusion. It was found that the amplitudes exceeding the critical level, the temperature dependence in a region temperature abnormal diffusion (TAD) in which the diffusion coefficient increases with decreasing temperature.
Temperature-abnormal diffusion in underdamped systems
Keywords: компьютерное моделирование; периодические структуры; уравнения Ланжевена; периодические поля; коэффициент диффузии; diffusion; computer simulation; periodic structures; Langevin equation; time-periodic fields